The Level Of Readiness Of Teachers In Vocational Colleges To The Implementation Of Online Teaching - Yunus, Faizal Amin Nur (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study aims to review the level of readiness of teachers at Vocational Colleges from the aspects of knowledge, skills and attitudes towards the implementation of online teaching. Therefore, a set of questionnaires consisting of three parts was used as a research instrument. A pilot study was conducted at Vocational Colleges around Johor and involved a total of 30 teachers. Based on the pilot study conducted, Cronbach’s Alpha coefficient values ​​for all questionnaire items have excellent reliability. In addition, the study sample consisted of 86 teachers at Vocational Colleges who were involved under the Mechanical and Manufacturing Department, namely Welding Courses, Refrigeration and Air Conditioning Courses, Industrial Machinery Courses and Automotive Courses in four schools around Johor, namely Vocational Colleges in Kluang, Colleges Vocational in Segamat, Kota Tinggi Vocational College and Muar Vocational College. The data obtained was analyzed with the help of computer software, which is the Statistical Package for Social Sciences (SPSS) version 23 program. The statistics used are descriptive statistics involving frequencies, mean scores and percentages. The average result of the mean score of the study shows that 3.11 for the level of knowledge, 3.00 for skills and 3.03 for the teacher’s attitude towards the implementation of online teaching is moderate. Therefore, it can be clearly concluded that the smooth implementation of online teaching cannot be fully achieved due to the factors of the level of knowledge, skills and attitudes of teachers in applying technology in education.